Correlation of Side Effects of ARV (Antiretroviral) Drugs with ARV Therapy Compliance in PLWHA at KDS Jombang Care Center Plus of Jombang Regency - Putri Dessyanti, Riska; Daramatasia, Wira; Yuliyanik, Yuliyanik (Universitas Nahdlatul Ulama Surabaya, 2024)
Human Immunodeficiency Virus (HIV) attacks white blood cells, leading to a weakened immune system. Acquired Immune Deficiency Syndrome (AIDS) refers to the set of symptoms caused by the decline in immunity due to HIV. Antiretroviral therapy (ART) is used to suppress viral replication, with treatment success largely dependent on adherence to therapy. However, side effects of antiretroviral drugs can negatively impact adherence by causing unwanted symptoms that discourage patients from continuing treatment. This study aims to analyze the correlation between the side effects of antiretroviral drugs and adherence to antiretroviral therapy among people with HIV/AIDS in the Jombang Care Center Plus Peer Support Community, Jombang Regency. This study used a cross-sectional design with purposive sampling, involving 38 respondents. Adherence to ART was assessed using the Morisky Medication Adherence Scale-8 (MMAS-8) questionnaire, while the side effects of antiretroviral drugs were evaluated using the Group Clinical Trial AIDS questionnaire. Statistical analysis was performed using Somers' D test. The Somers' D test showed a significant correlation between the side effects of antiretroviral drugs and adherence to therapy (p = 0.002, p < 0.05). This study concludes that side effects of antiretroviral drugs are significantly associated with adherence to antiretroviral therapy among people with HIV/AIDS in the Jombang Care Center Plus Peer Support Community.